CRISP-view: a database of functional genetic screens spanning multiple phenotypes. Issue Volume 49:Issue D1(2021) (3rd October 2020) - Cui, Yingbo; Cheng, Xiaolong; Chen, Qing; Song, Bicna; Chiu, Anthony; Gao, Yuan; Dawson, Tyson; Chao, Lumen; Zhang, Wubing; Li, Dian; Zeng, Zexiang; Yu, Jijun; et al.
Abstract: High-throughput genetic screening based on CRISPR/Cas9 or RNA-interference (RNAi) enables the exploration of genes associated with the phenotype of interest on a large scale. The rapid accumulation of public available genetic screening data provides a wealth of knowledge about genotype-to-phenotype relationships and a valuable resource for the systematic analysis of gene functions. Here we present CRISP-view, a comprehensive database of CRISPR/Cas9 and RNAi screening datasets that span multiple phenotypes, including in vitro and in vivo cell proliferation and viability, response to cancer immunotherapy, virus response, protein expression, etc. By 22 September 2020, CRISP-view has collected 10 321 human samples and 825 mouse samples from 167 papers. All the datasets have been curated, annotated, and processed by a standard MAGeCK-VISPR analysis pipeline with quality control (QC) metrics. We also developed a user-friendly webserver to visualize, explore, and search these datasets. The webserver is freely available at http://crispview.weililab.org .